Bactericidal Permeability Increasing Protein Gene Polymorphism is Associated with Inflammatory Bowel Diseases in the Turkish Population - EREN, FATİH; ATUĞ, ÖZLEN (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2015)
Background/Aims: Inflammatory bowel disease, a chronic inflammatory disease with unknown etiology, affects the small and large bowel at different levels. It is increasingly considered that innate immune system may have a central position in the pathogenesis of the disease. As a part of the innate immune system, bactericidal permeability increasing protein has an important role in the recognition and neutralization of gram-negative bacteria. The aim of our study was to investigate the involvement of bactericidal permeability increasing protein gene polymorphism (bactericidal permeability increasing protein Lys216Glu) in inflammatory bowel disease in a large group of Turkish patients. Patients and Methods: The present study included 528 inflammatory bowel disease patients, 224 with Crohn's disease and 304 with ulcerative colitis, and 339 healthy controls. Results: Bactericidal permeability increasing protein Lys216Glu polymorphism was found to be associated with both Crohn's disease and ulcerative colitis (P = 0.0001). The frequency of the Glu/Glu genotype was significantly lower in patients using steroids and in those with steroid dependence (P = 0.012, OR, 0.80; 95% confidence interval [CI]: 0.68-0.94; P = 0.0286, OR, 0.75; 95% CI: 0.66-0.86, respectively). There was no other association between bactericidal permeability increasing protein gene polymorphism and phenotypes of inflammatory bowel disease. Conclusions: Bactericidal permeability increasing protein Lys216Glu polymorphism is associated with both Crohn's disease and ulcerative colitis. This is the first study reporting the association of bactericidal permeability increasing protein gene polymorphism with steroid use and dependence in Crohn's disease.
Keywords: Bactericidal permeability increasing protein; inflammatory bowel disease; single nucleotide polymorphism; CROHNS-DISEASE; ULCERATIVE-COLITIS; BPI GENE; MUTATION; SUSCEPTIBILITY; VARIANTS; FRAGMENT; TOLL